Long-term outcomes amongst adults with anatomic repair for transposition of the great arteries: not as perfect as we would have hoped?. (25th November 2020) - Ladouceur, M; Hobbs, K; De Gonneville, A; Kempny, A; Iserin, L; Ly, R; Legendre, A; Rafiq, I; Dimopoulos, K; Li, W; Shore, D; Vouhe, P; et al.
Abstract: Background: The arterial switch operation (ASO) has replaced atrial switch procedures for D-transposition of the great arteries (D-TGA), with 90% of patients now reaching adulthood. However, patients may have residual lesions and/or sequelae, some of which may remain unrecognized, necessitating lifelong specialist surveillance. We examined the cardiac outcomes of a large number of contemporary ASO patients under tertiary adult congenital heart disease (ACHD) care. Methods: We examined late major adverse cardiovascular events (MACE) in adult TGA patients (>16 years) who underwent an ASO between 1981 and 2003 and continued their follow-up in 2 tertiary ACHD centers. MACE were defined as death, re-intervention, myocardial ischemia, arrhythmia, stroke/TIA, infective endocarditis and heart failure. Results: Overall, 199 patients (66% male, mean age 27±5 years) were followed in adult life for a median of 10 years [IQR 7–15] and were included in this study. Overall survival during this period was 99.5% (95% confidence interval [CI]: 94.4%-99.8%). Sixty-two (31.2%) patients experience MACE, including 52 reinterventions. MACE and reintervention-free survival at 20, 30 and 35 years were 87.6%, 58.6%, 50.6% and 89.5%, 69.1, 61%, respectively. Atrial arrhythmia was the most frequent cardiac event with an incidence of 5.5 cases per 1000 patient-years, whereas incidence of ventricular tachycardia and sudden cardiac death was 1.8‰ and 0.9‰ patient-years, respectively. Coronary artery disease was diagnosed in 6 (3%) patients, of whom 4 had symptoms, 1 had ST depression on ECG at rest and 3 had abnormal wall motion on echocardiography. The most frequent indication for reoperation was right ventricular outflow tract obstruction (n=35/52, 63.7%), whereas left ventricular outflow tract (LVOT) re-interventions rate increased significantly during adulthood compared to childhood from 1% to 5%, p=0.03 (Figure 1). On multivariate analysis, history of cardiac complications during infancy (HR 2.3, 95% CI:1.3–4.0, p<0.01) and uncommon coronary patterns (HR for type A versus B/C/D/E 0.47, 95% CI:0.26–0.83, p<0.01) were independent predictors of MACE in adulthood. At the latest follow-up, 90.9% of patients were functional class I, left ventricular ejection fraction was 59.6±6.5% and peak oxygen uptake 71.1±24.9% predicted. At least moderate neoaortic regurgitation and aortic dilatation (≥40mm) were present in 8.0% and 35.2%, respectively, with more than mild pulmonary stenosis in 19.6%. Conclusion: Adult patients with ASO for TGA have a low late mortality. However, MACE are common requiring reintervention, particularly for RVOT obstruction and neo-aortic valve dysfunction, the latter with rising rates during adulthood. Patients with cardiovascular complications during childhood are at the highest risk for MACE. All patients merit life-long tertiary care. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): Assistance Publique des Hôpitaux de Paris